1994
DOI: 10.1111/j.1365-2141.1994.tb06739.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor IX gene haplotypes in Brazilian Blacks and characterization of unusual Ddel alleles

Abstract: Analysis of factor IX gene polymorphisms is considered the best approach for prenatal diagnosis and carrier detection of haemophilia B when the identification of the gene mutation is not possible. Studies involving factor IX gene polymorphisms in Black populations are scarce and essentially restricted to the North-American Black population whose composition is substantially different from that of the Brazilian and presumably other Black populations of South America. In this paper we report the analysis of eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The entire ∼35 kb of the FIX gene has been sequenced, but no short tandem repeat polymorphisms have been found. However, the Dde I polymorphism in intron 1 is a complex repeat [25] having two common and several rare alleles and a Caucasian heterozygosity rate of 35%, making it a useful component of a panel of markers for linkage analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The entire ∼35 kb of the FIX gene has been sequenced, but no short tandem repeat polymorphisms have been found. However, the Dde I polymorphism in intron 1 is a complex repeat [25] having two common and several rare alleles and a Caucasian heterozygosity rate of 35%, making it a useful component of a panel of markers for linkage analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We were careful to try to exclude mulattos from the Black sample, although figures of estimated admixture with Caucasians are not available. A low admix ture with Caucasians is indicated by the close agreement of allele frequencies distribution of D1S80 and ApoB 3' VNTR with other Black populations, as well as by the results of analy sis of the factor VIII and factor IX genes poly morphisms in this population [36,41], Brazil ian Blacks are descendants of African slaves and are genetically very different from North American and Caribbean Blacks, as demon strated by the predominance of genes of Ban tu origin as compared with genes of Benin ori gin and very rare genes originated from the Senegambia [42], The Japanese sample com prised Japanese immigrants or their first-or second-generation descendants.…”
Section: Discussionmentioning
confidence: 99%
“…It was also mentioned that although the study of restriction fragment length polymorphisms is the preferred method in familial haemophilia, it is less useful in isolated cases [14]. DNA polymorphism studies also revealed that some single polymorphic sites can assess the carrier status up to approximately 30% whereas three or more probes can give the results up to 90% [15][16][17][18][19]. In another study, racial variations were also seen, i.e.…”
Section: Resultsmentioning
confidence: 99%